Combination therapy with oncolytic viruses for lung cancer treatment - Sun, Lei; Zhao, Qi; Miao, Liyun (Frontiers in Oncology, 2025)
Lung cancer is the leading cause of cancer-related death globally. Despite various treatment options, adverse reactions and treatment resistance limit their clinical application and efficacy, therefore, new effective treatment options are still needed. Oncolytic viruses (OVs) are a new anti-cancer option. With a powerful anti-tumor effect, OVs are gradually being applied to the treatment of solid tumor. In clinical practice, we have found that in patients with NSCLC and SCLC, OVs combined with immune checkpoint inhibitors (ICI) treatment make tumor with poor response to immunotherapy become sensitive. Furthermore, studies have shown that OVs combined with chemotherapy, radiation therapy, and other immune approaches (such as anti-pd1 drugs) have synergistic effects. These studies suggest that OVs combined therapy may bring hope for the treatment of lung cancer patients. This article will review the current status and prospect of OVs combination therapy in the field of lung cancer treatment and summarizes the mechanism of action.